Riwayat status gizi, pemberian ASI eksklusif dan kejadian diare pada balita - Priyo Sasmito; Destiana Setyosunu; Irmawati Sadullah; Ramdhani Muhammad Natsir; Agung Sutriyawan (Holistik Jurnal Kesehatan, 2023)
Background: The incidence of diarrhea is the second cause of death in children under 5 years. Emergency diarrhea events are caused by nutritional status and not exclusive breastfeeding of children, so the incidence of diarrhea in toddlers is still a problem.Purpose: To determine the relationship between nutritional status and exclusive breastfeeding with emergency diarrhea events in toddlersMethod: Using a correlational descriptive design with a retrospective, with cases and a control. The cases population is toddlers who have diarrhea and the control population there are toddlers who do not have diarrhea. Samples were taken as many as 70 toddlers. The instrument used is a questionnaire. The existing collection technique used is purposive sampling. Data analysis using chi-square test.Results: The results of this study showed that there was a relationship between nutritional status and the incidence of diarrhea in toddlers (p=0.007, OR=6.1), and there was an exclusive relationship between breastfeeding and the incidence of diarrhea in toddlers (p=0.001, OR=8.0).Conclusion: The case group had more toddlers with abnormal nutritional status than the control group, and toddlers who did not get exclusive breastfeeding were higher than the control group, so toddlers with abnormal nutritional status and did not get exclusive breastfeeding were more likely to suffer from diarrhea as toddlers.Suggestion: It is recommended to health workers to conduct health education to the community, especially efforts to improve nutrition in children and exclusive breastfeeding.Keywords: Diarrhea; Exclusive Breastfeeding; Nutritional Status; ToddlerPendahuluan: Kejadian diare menjadi penyebab kematian kedua pada anak di bawah 5 tahun. Kegawatdaruratan kejadian diare disebabkan oleh status gizi dan tidak diberikannya ASI eksklusif pada anak, sehingga kejadian diare pada balita masih menjadi permasalahan.Tujuan: Untuk mengetahui hubungan status gizi dan ASI eksklusif dengan kegawatdaruratan kejadian diare pada balita.Metode: Menggunakan desain diskriktif korelational dengan retrospektif, menggunakan kasus and control. Populasi kasus adalah balita yang mengalami diare dan populasi kontrol ada balita yang tidak mengalami diare. Sampel diambil sebanyak 70 balita. Instrument yang digunakan adalah kuesioner. Teknik pengumpulan data yang digunakan adalah purposive sampling. Analisis data menggunakan uji chi-square.Hasil: Hasil penelitian ini menunjukkan bahwa ada hubungan status gizi dengan kejadian diare pada balita (p=0.007, OR=6.1), dan ada hubungan ASI eksklusif dengan kejadian diare pada balita (p=0.001, OR=8.0).Simpulan: Kelompok kasus lebih banyak balita dengan status gizi tidak normal dibandingkan kelompok kontrol, dan balita yang tidak mendapatkan ASI eksklusif lebih tinggi dibandingkan dengan kelompok kontrol, sehingga balita dengan status gizi tidak normal dan tidak mendapatkan ASI eksklusif lebih berpeluang menderita diare saat balita.Saran: Disarankan kepada tenaga kesehatan untuk melakukan pendidikan kesehatan kepada masyarakat khususnya upaya perbaikan gizi pada anak dan pemberian ASI eksklusif.